Parental attitude and awareness toward preventive dentistry in Riyadh, Saudi Arabia: A cross-sectional study - Sultan A Almalki; Majed S Almutairi; Abdulmajeed Mohammed Alotaibi; Ahmed Saleh Almutairi; Lafi Muqbil ALbudayri; Ramzi Zayed Almutairi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Preventive oral health of a child is dependent on the parental knowledge toward caries control, care of deciduous tooth, use of space maintainers for malocclusion, and utilization of various procedures available for preventing oral diseases by oral health professionals. This study was aimed to assess the attitude and awareness of preventive dentistry among parents residing in Riyadh city, Kingdom of Saudi Arabia. Methodology: A cross-sectional, questionnaire study was conducted among 300 male parents. Questionnaire was sent through the use of social media, and responses were collected. Results: Seventy-four percent of male Saudi parents were aware of prevention of oral diseases. 38.45% of male parents were aware of preventive dentistry procedure, but preventive dentistry utilization rate was seen among 6% population only. Attitude toward the prevention of oral disease was statistically not significant according to the age group and income but statistically significant according to education. The utilization of preventive procedures was significant according to education and income (P < 0.05). Conclusion: Awareness about preventive dentistry was more among Saudi parents but utilization rate was directly correlated to their education and income. After The utilization of preventive procedures was significant according to education and income (P < 0.05).